Meta-Analysis: The Influence of Innovative Learning Models on High School Students' Biology Learning Outcomes - Az-Zahra, Rania; Fajri, Amalia; Nurfadhila, Devi; Harefa, Krisdayani; Ristanto, Rizhal Hendi; Isfaeni, Hanum (JURNAL BIOEDUCATION, 2025)
Learning is considered effective and efficient when it achieves a level of attainment that exceeds established standards. Innovative learning is a new approach or idea used to support students' development in the learning process and its outcomes. The purpose of this study is to determine the effectiveness of creative classroom learning models and new learning models. This research employed a quantitative method using meta-analysis on 22 experimental research results obtained from domestic and international academic journals. Based on effectiveness calculations by grade level, Class XI scored higher than Class X, with a score difference of 0.87. With an effect size of 1.72, Guided Inquiry was the most influential type of innovative learning. The syntax of this type encourages students to participate actively in learning. This indicates that innovative learning models have a significant impact on learning outcomes. Therefore, this learning model can be beneficial for biology education.